Efektivitas Program Eco-Pentren Dan Aplikasi SampahKita Dalam Pelestarian Lingkungan Di Mambaul Ulum Bata-Bata - Sri Ira Suharwati; Fadolul Ghafur Moh. Ihsan Zain; Moh. Ihsan Zain (IAIN Madura, 2026)
The level of public awareness regarding environmental sustainability, particularly in waste management at Mambaul Ulum Bata-Bata, remains relatively low. The gap between theoretical understanding and practical application in the field is an issue that must be addressed. To address this issue, the Eco-Pentren program can be implemented, along with the use of the SampahKita app in partnership with the Hamdalah waste management service. This study employs a quantitative approach using data collection techniques such as pre-test and post-test assessments, as well as documentation. The study sample consists of 43 students/pupils from Mambaul Ulum Bata-Bata selected at random. Data were analyzed using frequency distributions with the aid of basic SPSS. The research results indicate that the implementation of the Eco-Pentren program and the SampahKita app proved effective at a rate of 72.1%. It was deemed effective due to changes in student behavior, including active participation in the “Clean Morning” and “Blessed Friday (School Cleanup)” programs as well as their practice of the 5R principles, maggot farming, active participation in scientific writing activities on environmental themes, and the formation of a special task force (LHB Task Force) whose members consist of administrators and religious instructors who address environmental issues in a structured manner.